Effect of dietary probiotics intake on cancer mortality: a cohort study of NHANES 1999–2018 - Yang Yang; Mengshu Pan; Xi Xia; Jiajing Liang; Xiangxiang Yin; Qian Ju; Jiqing Hao (Scientific Reports)
Abstract Limited research has explored the connection between consuming dietary probiotics in the diet and cancer-related deaths. This study aimed to examine how the intake levels of three different groups of dietary probiotics are associated with the risk of dying from cancer in a representative sample of adults in the United States. Using data from the USDA Food Survey Nutrient Database, researchers categorized foods based on their microbial levels as low (104 CFU/g), medium (104–107 CFU/g), or high (> 107 CFU/g). They then used Cox proportional risk regression models to assess the risk of cancer-specific death, with follow-up periods until December 31, 2019. The study included 36,894 participants aged 20 and older, representing 148,639,331 U.S. citizens. After adjusting for various factors, the results showed that low and moderate intake of probiotics significantly reduced the risk of cancer mortality, with no significant association found for high probiotic intake. The findings suggest a notable link between dietary probiotics and cancer-specific mortality, highlighting the potential impact of dietary choices on cancer survival and indicating areas for healthcare interventions.